From Exclusion to Inclusion: Changes in Women's Roles in Folk Sports and Indigenous Physical Culture in China. Issue 15 (2nd November 2018) - Xiong, Huan; Deng, Junyu; Yuan, Jiao
Abstract: The physical culture of Chinese folk sports is embedded in religions and rituals that have been predominantly ruled by men. However, this situation has been changing as the forms and meanings of folk sports transform in modern China. Based on the literature and interviews, in this research, the Funeral Dance of the Tujia ethnic group was considered as a case to explore how gender roles in Tujia indigenous physical activity changed during the modernizing process. Given the transformation of Funeral Dance from an indigenous funeral ritual to a national fitness programme and public and commercial performances, Tujia women have gained social access, legal status, national identity, and value, allowing them to participate in the dance. Policy interventions, capitalist drive, and social progress constituted an integral force that has systematically challenged the engendered nature of Chinese folk sports. Nevertheless, in Tujia's conceptual framework, there is an invisible curtain between the stage and backstage of Funeral Dance performances. In the 'front', the participation of women is fully encouraged; however, 'backstage', the gender taboo remains as a so-called sporting tradition. The inclusion of both genders in folk sports is an unavoidable tendency in China, though the gendered boundaries continue to impact on women's participation.